Effect of Different Types of Bracing System and Shear Wall on the Seismic Response of RC Buildings Resting on Sloped Terrain - M. Y. Laissy (Salehan Institute of Higher Education, 2022)
Several factors have been affecting the urban design areas, leading to the construction of reinforced concrete (RC) buildings. Buildings on sloped terrains have been gaining increased popularity, especially from architectural peers. The vulnerability of constructions to seismic loads on sloped terrains increases due to mass and vertical irregularity, which in turn increases the torsional moments as well as shear forces. To control the effect of the seismic loads, many systems have been implemented, including shear walls and bracing systems. The objective of this work is to evaluate the effects of different strengthening systems and to identify the most suitable one for seismic load resistance. This paper studies the behavior of buildings with different strengthening systems applied to seismic loads using ETABS V18.1 and response spectrum analysis. A parametric study for these buildings has been performed to evaluate the effect of seismic loads on them. A dynamic analysis of the buildings in terms of shear forces, displacement, drift, fundamental time period, base shear, and story stiffness was carried out. The results demonstrated that the use of a combined strengthening system increased the stiffness and stability of the models and the resistance of RC buildings to seismic loads on sloped terrains. Doi: 10.28991/CEJ-2022-08-09-014 Full Text: PDF